Retrieval of lysosomal membrane and acid phosphatase from phagolysosomes of Paramecium caudatum (The Rockefeller University Press, 1984)
Little is known about the fate of lysosomal membrane in phagocytic cells. Because the age of the digestive vacuoles in Paramecium caudatum can be easily determined, we have been able to study the dynamic membrane events in the older vacuoles. Late in the phagolysosomal stage (DV-III) the vacuole membrane undergoes a burst of tubule formation. The tubules expand into vesicles which have characteristics resembling lysosomes in both thin sections and freeze-fracture replicas. The tubules also contain acid phosphatase activity when they arise from acid phosphatase-reactive vacuoles. We conclude that after active digestion lysosomal membrane is retrieved in whole or in part along with some membrane-associated hydrolases. A logical extension of these results is that the lysosome-like vesicles, after being recharged with hydrolases by fusing with primary lysosomes, are recycled back to DV-II for reuse.